Search and Seizure Data, 1963 - Nagel, Stuart S. ([Verlag nicht ermittelbar], 1984)
This data collection contains information gathered about search and seizure policies and practices in a 1963 survey administered to one police chief, prosecutor, trial court judge, defense attorney, and American Civil Liberties Union (ACLU) official in each of the 50 states. Respondents answered questions about the practices of various criminal justice decision-makers in the handling of search and seizure evidence since the 1961 Supreme Court decision requiring all states to exclude illegally seized evidence from courtroom proceedings. Questions were also asked concerning the knowledge and values of the respondents, and the use of civil and legal action to deter illegal searches. The file also contains non-survey demographic data about the characteristics of each state.